KONSEP KESELAMATAN MASYARAKAT KAWASAN ADAT KAJANG DALAM TRADISI ANGNGANRO ( ANALISIS URF’) - Laman, Ilham; Widyani, Sri (DISCOURSE: Indonesian Journal of Social Studies and Education, 2023)
This article discusses the Angnganro Tradition in the Community of Kajang District, Bulukumba Regency from the Perspective of Islamic Law. The type of research is qualitative field research, with a legal sociology research approach. Legal sociology approach, namely the approach used to find out how the facts that occur in the field are related to the traditions of the local community. The results of this study indicate that the angnganro tradition is a ceremony of releasing vows or a ceremony of giving thanks because one's prayers and requests have been answered. For example, a person is affected by a disaster or a dangerous disease and then he prays that if he is safe from harm or recovers from his illness, he will carry out the "angnganro" ritual, this ritual is a form of gratitude to God Almighty as the owner of the universe and everything in it. The angnganro tradition as a traditional ritual performed by the Kajang indigenous people illustrates to the Indonesian people that belief in traditional rituals is not polytheism but as an instrument of liaison with the owner of the universe, namely Allah. because what is done is inseparable from Islamic values.